Application of chicken dung and rice husk biochar as soil amendments for improvement of soil properties and growth performance of Andrographis paniculata (hempedu bumi) in an organic system - Raja Yahya, Raja Nur Atikah (2015)
The demand for medicinal plant-based raw materials, including organic herbs, is growing at the rate of 15 to 25 percent annually in Malaysia. Andrographis paniculata (hempedu bumi) is one of the high value herbal crop. However, the production is still in a small scale in Malaysia. Besides, the low fertility status of Malaysian soils is one of the problem that causes low crop performance. Hence, proper soil amendment capable to improve the soil are needed to assure the production of high quantity and quality of A. paniculata in Malaysia. Application of chicken dung as a basal is a common soil amendment that has been used in agriculture crops. It is due to the availability in the market and gives fast respond to the plant by uptake of nitrogen and phosphorus in agricultural soils. On the other hand, biochar is recently a popular soil amendment such as rice husk biochar that is reported to hold nutrients, reduce leaching of nitrogen into the ground water and decrease soil acidity. Therefore, the objective of this study is to determine the optimum rate of chicken manure and rice husk biochar for high yield of A. paniculata. There were 9 different treatments, 3 different rates of chicken manure (0 t/ha, 2.5 t/ha, 5 t/ha) and 3 rates of rice husk biochar (0 t/ha, 5 t/ha and 10 t/ha), with 4 replications and 36 a total of experimental units; with two plants per-replication. The study was arranged in a complete randomized block design (RCBD). The soil used for this study has a texture of 62.99% of clay, 6.51% of silt, and 30.51% of sand was taken from Ladang 16, Fakulti Pertanian, is used for preparation of 8kg soil per polybag as a media. After germinating the seeds for one month, the seedlings were transplanted into the polybags which have been mixed with chicken manure and rice husk biochar a week before. Organic fertilizer Bokashi (150 kg N/ha) was applied to all experimental units during transplanting. The plants were irrigated manually twice a day and weeding was done once a week. Plants were harvested on week 8 from transplanted day. The soil samples before planting and after harvest were analyzed. The soil used were analyzed for pH, exchangeable bases, available P, CEC, total N and total C. The plant growth parameters were measured every 2 weeks; plant height, plant canopy diameter, number of branches, total biomass, fresh and dry weight and shoot to root ratio. SAS software wer used as statistical analysis. The result showed that the application of chicken dung at 5 t/ha and rice husk biochar at 5 t/ha was the optimum rate to increase the biomass production of the plants. Applying chicken dung and rice husk biochar to the soil improved its properties. There were significant differences showed on the soil pH, available phosphorus, and exchangeable base calcium and magnesium. Total carbon, total nitrogen, carbon to nitrogen ratio, exchangeable base potassium, and cation exchange capacity showed non significant and does not differed much from control might be due to leaching and uptake by plants. The application of chicken manure and rice husk biochar have improved the performance and yield of A. paniculata and improved the soil chemical properties especially in shoot biomass and soil pH.